Ground-level Particulate Sulphate and Gaseous Sulphur Dioxide Downwind of an Aluminium Smelter - Dane Blanchard; Julian Aherne (Aerosol and Air Quality Research)
Abstract Particulate sulphate (pSO4 2−) is an atmospheric pollutant known to affect human/environmental health and global radiative-forcing. The Rio Tinto (RT) aluminium smelting facility in Kitimat, British Columbia, is the primary source of sulphur dioxide (SO2) emissions to the surrounding Kitimat Valley, a relatively isolated and unpolluted region. A network of active two-stage filter-packs and passive-diffusive samplers was established between June 2017 to October 2018 with the objective to evaluate the spatiotemporal variation and relative contribution of pSO4 2− to total anthropogenic atmospheric oxidized sulphur (SOx = SO2 + pSO4 2−). Average pSO4 2− across all sites (n = 9) was 0.41 µg m−3 (24–48 hour exposures) and ranged from 0.03 to 2.03 µg m−3. In contrast, average filter-pack SO2 ranged from 0.11 to 8.9 µg m−3 (during the same exposure periods). The filter-pack pSO4 2−/SOx concentration ratio (Fs) increased downwind of the smelter, indicating that the relative concentration of pSO4 2− increased with distance from the smelter. Furthermore, the increasing pSO4 2−/vanadium (V) ratio (used as a tracer of smelter emissions) relative to distance confirmed particulate formation was occurring within the emission plume during the sampling period. Irrespective of in-plume aerosol formation, pSO4 2− contributed a relatively minor fraction of total atmospheric SOx within the emission plume (field campaign averages Fs < 20%; pSO4 2− < 0.1 µg S m−3; SO2 > 1.0 µg S m−3).